Spatial localization in manufacturing: A cross-country analysis - Stefania Vitali; Mauro Napoletano; Giorgio Fagiolo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2009)
This paper employs a homogenous firms database to investigate industry localization in European countries. More specifically, we compare, across industries and countries, the predictions of two of the most popular localization indices, i.e., the Ellison and Glaeser index (Ellison and Glaeser, 1997) and the Duranton and Overman index (Duranton and Overman, 2005). We find that, independently from the index used, localization is a pervasive phenomenon in all countries studied, but the degree of localization is very uneven across industries in each country. Furthermore, we find that the two indices significantly diverge in predicting the intensity of the forces generating localization within each industry. Finally, we perform a crosssectoral analysis of localized industries. We show that, in all countries, localized sectors are mainly 'traditional' sectors (like jewelery, wine, and textiles) and sectors where scale economies are important. However, once one controls for countries' industrial structures science-based sectors turn out to be the most localized ones.
Keywords: R12; R3; 330; Industry Localization; Manufacturing Industries; Localization Indices; Spatial Concentration; Spatial correlation; Cross-country studies